2022
DOI: 10.1088/2043-6262/ac6c22
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of gallic acid loaded carboxymethyl chitosan nanoparticles as drug delivery system for cancer treatment

Abstract: Gallic acid (GA) is a natural phenolic compound with antioxidant, anti-proliferative, and anticancer effects. However, the potential of GA as an anticancer agent is restricted by its poor absorption, rapid elimination, and low bioavailability. Nanostructure-drug carriers have opened up a new field in cancer therapy by improving the efficacy of drugs. In this work, we developed a nanoformulation of GA in carboxymethyl chitosan (CMC). The particle size, surface charge and molecular structure of the CMC NPs loade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The proposed targeting of cancer stem cells should reduce cancer initiation, progression, and metastasis. Among other active antitumor agents, gallic acid was successfully loaded in carboxymethyl CS NPs to increase its absorption and bioavailability [ 100 ], while ellagic acid-loaded CS NPs were coated with tween-80 to increase their therapeutic effect against breast cancer [ 101 ].…”
Section: Cs Np Platforms For a Specific Drug Deliverymentioning
confidence: 99%
“…The proposed targeting of cancer stem cells should reduce cancer initiation, progression, and metastasis. Among other active antitumor agents, gallic acid was successfully loaded in carboxymethyl CS NPs to increase its absorption and bioavailability [ 100 ], while ellagic acid-loaded CS NPs were coated with tween-80 to increase their therapeutic effect against breast cancer [ 101 ].…”
Section: Cs Np Platforms For a Specific Drug Deliverymentioning
confidence: 99%
“…The ATR FTIR spectra of the Alg-NPs, Alg-PPE NPs and PPE were obtained using an ATR-FTIR (Bruker VERTEX 80, Germany) spectrophotometer associated with Platinum Diamond ATR-disc as an internal reflector. The samples were introduced onto the ATR crystal followed by acquisition of FTIR spectra over the scanning variety of 400-000 cm−1 at a resolution of cm-1 [19] .…”
Section: Attenuated Total Reflection-fourier Transform Infrared Spect...mentioning
confidence: 99%
“…With a small range of 20-200 nm, nanoparticles easily travel and accumulate inside the interstitial cavity of the tissue to deliver drugs to specific sites that are beneficial in the treatment of diseases including cancer, infections, and gene therapy, as well as diagnostic applications [9,10]. Some studies have been carried out to develop nanosystems of anti-cancer plantderived compounds such as camptothecin [11], garlic acid [12] and honokiol [13][14][15] for cancer treatment, especially honokiol. In a study by Lou et al, honokiol-loaded liposomes were found to demonstrate efficient anti-angiogenesis and inhibition (84%-88% compared to controls) on tumour growth in both cisplatin-sensitive (A2780s) and cisplatinresistant (A2780cp) tumour-bearing mice [13].…”
Section: Introductionmentioning
confidence: 99%